Hydration status and running performance during cool and hot training sessions in rugby union forwards and backs - Hoshi, D.; Tamai, S.; Kuroki, T.; Kim, H.; Okada, S.; Shimasaki, T.; Watanabe, K. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Rugby showed a high incidence of exertional heatstroke. Different physiques and running performances between the forward and back players (FW and BK) may result in different heatstroke risks. This study aimed to compare the hydration status, running performance, and perceived heatstroke symptoms (PHS) between cool and hot environment training (HT and CT) in university rugby union FW and BK. METHODS: Thirteen university rugby players (seven forwards and six backs) participated in this study. During both conditions, players were allowed to drink water and sports drink, and the amount of fluid intake was recorded. Body mass was measured pre- and post-training, and weight loss was calculated. Sweat loss was calculated based on body mass and fluid intake. During training, running performance was measured using GPS. The presence of PHS was assessed using a questionnaire administered after training. RESULTS: Fluid intake and sweat loss were higher in the HT as opposed to the CT, and FW showed higher fluid intake and dehydration than BK. However, there were no significant differences in weight loss observed during data collection. Running distance per minute and maximum speed were higher in BK than in FW, but there was no significant difference between conditions. Although a significant weight loss was not observed between conditions, the number of PHS was higher in the HT. CONCLUSIONS: Although BK had a higher running distance and maximum speed than FW during training, a higher cycle of fluid intake and sweat loss was observed in the FW than that in the BK.